WHAT AUDIT FEATURES IMPACT VALUE RELEVANCE OF ACCOUNTING INFORMATION? - Angelina, Aurelia; Setiawan, Yan Christianto (Jurnal Akuntansi Kontemporer, 2024)
Research Purposes. The objective of this research is to ascertain how audit quality affects the value and relevancy of accounting data, where audit quality is proxied by audit company size, audit partner gender, audit fees, audit reporting delays, and auditor opinion.Research Methods The study examining the relationship between variables using a fixed-effects model focuses on 780 non-financial corporations registered on the Indonesia Stock Exchange between 2020 and 2021, chosen through non-probability-purposive-judgment sampling techniques.Research Results and Findings. The study's conclusions indicate that while audit fees and latency in reporting can decrease the value relevance of accounting information, public accounting firms associated with the Big Four and the presence of female audit partners can enhance it. Additionally, the auditor's opinion section yields some intriguing results, as it increases the relevance of book value while decreasing that of profit value.